Case Studies and Evaluation of Green Mining considering Uncertainty Factors and Multiple Indicator Weights. (12th October 2020) - Wang, J.; Hu, B.; Chang, J.; Wang, W. P.; Li, H. L.
Abstract : The implementation of green mining (GM) can improve the quality of economic growth. Based on uncertainty measurement theory (UMT), we aim to develop a reasonable method of green mining (GM) evaluation for building material (BM) mines via comparative analysis. At first, establish UMT evaluating model for GM. The linear uncertainty (LU) measurement function was employed to solve single indicator measure values. Then, based on the entropy weight method (EWM), the analytic hierarchy process (AHP) and a method that couples AHP and EWM (EWM-AHP), and the weights of the evaluating indicator were determined. At last, based on UMT, a total of 6 coupled methods are developed to evaluate the GM grades. The GM grades of two building material mines in China were evaluated by applying the 6 methods. Future suggestions were given to the enterprises to improve the GM grades. According to the actual situations of GM in the two building material (BM) mines, it can be speculated that UMT-EWM-AHP-CDRT is the most reasonable method. The reasonable method can not only evaluate the GM grades for BM but also provide guidance to the development of GM for BM.